PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PENGGUNAPADA APLIKASI PRO-DENPASAR DI KOTADENPASAR - Syafitri, Aulia Dewi; Purnamaningsih, Putu Eka; Yudartha, I Putu Dharmanu (CITIZEN CHARTER; Vol 2 No 1 (2022): Administrasi Publik 2022, 2022)
PRO-Denpasar application on aims to accommodate and handle all public complaints in Denpasar City. Of course, this application is an alternative in the midst of the Covid-19 pandemic because with this application, people get services online. Therefore, the service expecte d by the community is quality service by prioritizing user satisfaction. The method used by the author is the Quantitative method with the Probability Sampling technique using SPSS data from the questionnaire distribution. The theoretical basis used is service quality according to Parasuraman 2013 there are five indicators: reliability, responsiveness, certainty, empathy, form and using user satisf action theory according to Kotler and Keller 2012 there are 5 indicators: conformity of expectations, recommendations, loyalty, interest in returning, and system complain. The results obtained are that there is a correlation of 0.776 with a strong relationship level (Sugiyono, 2013) so that hypothesis 1 is accepted, which means that there is an influence of service quality on user satisfaction on the PRO-Denpasar application in Denpasar City, amounting to 60.2%. Keywords: Service Quality, PRO-Denpasar Application, Satisfaction